Nutritional prevention of cognitive decline and dementia - Dominguez, Ligia J.; Barbagallo, Mario (Acta Biomedica Atenei Parmensis, 2018)
Cognitive impairment results from a complex interplay of many factors. The most important independent predictor of cognitive decline is age but other contributing factors include demographic, genetic, socio-economic, and environmental parameters, including nutrition. The number of persons with cognitive decline and dementia will increase in the next decades in parallel with aging of the world population. Effective pharmaceutical treatments for age-related cognitive decline are lacking, emphasizing the importance of prevention strategies. There is extensive evidence supporting a relationship between diet and cognitive functions. Thus, nutritional approaches to prevent or slow cognitive decline could have a remarkable public health impact. Several dietary components and supplements have been examined in relation to their association with the development of cognitive decline. A number of studies have examined the role of dietary patterns on late-life cognition, with accumulating evidence that combinations of foods and nutrients may act synergistically to provide stronger benefit than those conferred by individual dietary components. Higher adherence to the Mediterranean dietary pattern has been associated with decreased cognitive decline and incident AD. Another dietary pattern with neuroprotective actions is the Dietary Approach to Stop Hypertension (DASH). The combination of these two dietary patterns has been associated with slower rates of cognitive decline and significant reduction in incident AD. This review evaluates the evidence for the effects of some dietary components, supplements, and dietary patterns as neuroprotective, with potential to delay cognitive decline and the onset of dementia.